First observation of the decay B0s → φK[bar]*0 - Aaij, Roel; Aquines Gutiérrez, Osvaldo; Bachmann, Sebastian; Bien, Alexander; Blouw, Johan; Britsch, Markward; Di Canto, Angelo; Dordei, Francesca; Färber, Christian; Fontana, Marianna; Gersabeck, Evelina; Grünberg, Oliver; et al. (Journal of high energy physics, 2013)
Abstract:The first observation of the decayB0s→φK∗0 is reported.Theanalysis is based on a data sample corresponding to an integrated luminosity of 1.0 fb−1of pp collisions at√s= 7 TeV, collected with the LHCb detector. A yield of 30±6B0s→(K+K−)(K−π+) decays is found in the mass win-dows 1012.5< M(K+K−)<1026.5 MeV/c2 and 746< M(K−π+)<1046 MeV/c2. The signal yield is found to be dominated by B0s→φK∗0 decays, and the corresponding branching fraction is measured to be B(B0s→φK∗0)= (1.10±0.24 (stat)±0.14 (syst)±0.08 (fd/fs))×10−6, where the uncertainties arestatistical, systematic and from the ratio of fragmentation fractions fd/fs which accounts for the different production rate of B0 and B0s mesons. The significance of B0s→φK∗0 signal is 6.1 standard deviations. The fraction of longitudinal polarization in B0s→φK∗0 decays is found to be f0= 0.51±0.15 (stat)±0.07 (syst).